The Link Between Creativity, Cognition, and Creative Drives and Underlying Neural Mechanisms - Khalil, Radwa; Godde, Ben; Karim, Ahmed A. (Frontiers in Neural Circuits, 2019)
Having a creative mind is one of the gateways for achieving fabulous success and remarkable progress in professional, personal and social life. Therefore, a better understanding of the neural correlates and the underlying neural mechanisms related to creative ideation is crucial and valuable. However, the current literature on neural systems and circuits underlying creative cognition, and on how creative drives such as motivation, mood states, and reward shape our creative mind, through the associated neuromodulatory systems (i.e., the noradrenergic (NE), the dopaminergic (DA) and the serotonergic (5-HT) system), seems to be insufficient to explain the creative ideation and production process. One reason might be that the mentioned systems and processes are usually investigated in isolation and independent of each other. Through this review, we aim at advancing the current state of knowledge by providing an integrative view on the interactions between neural systems underlying the creative cognition and the creative drive and associated neuromodulatory systems.